Myanmarina diversa sp. nov (Hymenoptera, Myanmarinidae) from mid-Cretaceous Kachi amber, northern Myanmar. (December 2022) - Zheng, Yan; Hu, Haiyan; Wang, Han; Chen, Jun; Zhang, Qi; Zhang, Haichun; Rasnitsyn, Alexandr P.
Abstract: Myanmarina as a small genus has received attention since 2017 as well as the new family Myanmarinidae of basal apocritan wasps was erected by Zhang & Rasnitsyn. Myanmarina diversa sp. nov is the sixth myanmarinid wasp, is described and illustrated from mid-Cretaceous Kachin amber. The new species is characterized by male antenna with 13 antennomeres and mid femur with posterior apical tooth. We also provide the comparison of characters among six Myanmarina species and discuss their possible biology.